The effect of external illumination on CSV-1000 contrast sensitivity measure among young adults/ Azmir Ahmad, Norfaridah Abdul Aziz and Nor Hanani Ozali - Ahmad, Azmir; Abdul Aziz, Norfaridah; Ozali, Nor Hanani (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Contrast played a major role in determining object appearance in vast areas, from medical perspectives to daily living activities such as driving. There were various clinical tests to measure contrast sensitivity which was designed to be used either with internal illumination or under external illumination. This study was aimed to compare the contrast sensitivity measurement between external and internal illuminated CSV-1000 and external illuminated FACT among young adults. A total of 38 participants of 22.05-year-old (±1.958), with best-corrected visual acuity of 6/6 were included in this study. They had best-corrected visual acuity of 6/6 with no history of ocular disease and binocular problem. The contrast sensitivity of different spatial frequencies, namely 3 cycles per degree (cpd), 6 cpd, 12 cpd and 18 cpd were measured under normal illuminated clinical room based on three conditions; external illuminated FACT screen, external illuminated CSV-1000 and internal illuminated CSV-1000. The measurement of contrast sensitivity was taken 3 times to produce an average contrast sensitivity value. Based on the Kruskal-Wallis non-parametric test, there was a statistically significant difference in contrast sensitivity only for external illuminated CSV-1000 at 6 cpd (p < 0.05). However, for 3, 6 and 18 cpd, in addition to other testing conditions, there were no significant differences (p > 0.05). The external illumination on CSV-1000 might produce glare during the contrast sensitivity measurement. Thus, external illumination affected the discrimination of contrast at moderate level of spatial frequencies only for CSV-1000. The contrast sensitivity measurement for CSV-1000 was more accurate under its internal illumination.